Pathogenesis of mycobacterium tuberculosis in rabbits (Experimental Model for Human Disease) - Imad Ibrahim Ali Al-Sultan; S.M.Al- Jamal (2011)
Experimental model using adult rabbits to investigate pathogenesis and ill effect of M.tuberculosis was worked up. Three groups of rabbits used each group eight in number. Animals in groups one and two were injected intraperitoneally with 1mg/ml/animal of the bacterium containing 2x10 CFU/ml. The third groups were left as control. Pathological changes were seen after sixty days of infection in the visceral organs in both groups infected. Immediately following the appearance of lesions, animals of groups one treated with Isoniazide and Rifampicine for two months. Sacrification of rabbits after 120,130 &140 days post infection of both groups envisages no typical lesions of tuberculosis in group one in contrast to the formation of clear and evident typical tubercles in group two. Histopathology revealed well established allergic inflammation and histiocytic granulomas of atypical tuberculosis infection predominantly in some internal organs (lung, liver. spleen & lymph nodes) in group one which is treated with TB-regimen while typical TB-granulomas were markedly established in various internal organs of group two infected with M.tubercolosis only. The non typical tuberculomas and inflammatory changes with tissue reaction in group one treated rabbits indicate a paradoxical lesion which gives such a non familiar tuberculoied lesion behavior. Rabbits as an experimental animal model proved to be an attractive model in study tuberculosis especially in the aspect of pathogenesis or treatment response because rabbits have disease manifestations and pathology similar to those noted in humans. Establishment of a rabbit model to study M.tuberculosis infection and treatment with anti-tuberculosis drugs can allow an important opportunity to investigate